Rancang Bangun Simulator Modul Kendali untuk Motor Operasi Katub Sebagai Media Pembelajaran Bagi Para Teknisi Baru di PLTU Nagan Raya - Eko Prasetyo Hadi; Hamdani Hamdani; Ahmad Dani (Pusat riset dan Inovasi Nasional, 2026)
The Motor Operated Valve (MOV) is a critical component in fluid control systems at Steam Power Plants (PLTU). Training new technicians is often hindered by limited access to actual equipment and operational safety risks. This research aims to design and develop an Arduino-based MOV control module simulator capable of simulating basic functions such as open, close, stop, and limit switch responses. The method used is Research and Development (R&D) with an experimental approach. The simulator was tested using a DC motor as the simulated valve actuator, equipped with push buttons, relays, limit switches, and indicator lamps for visual feedback. The test results showed that the simulator successfully represented control functions with 100% accuracy in limit switch responses and consistent operation. User evaluations involving ten new technicians indicated an 85% satisfaction rate in terms of ease of understanding and operational safety. This simulator has proven to be an effective, interactive, and safe learning medium for new technicians at PLTU Nagan Raya.